Insight into Nigeria’s progress towards the universal coverage of reproductive, maternal, newborn and child health services: a secondary data analysis - Xiaohui Wang; Joy James Mafiana; Xiping Shen; Wenping Hu (BMJ Open)
Objective This study investigated the progress towards the universal coverage of reproductive, maternal, newborn and child health (RMNCH) services in Nigeria after universal health coverage (UHC) adoption.Design A descriptive observational approach was used based on secondary data analysis. Representative data generated from publicly accessible databases and reports were used to describe the coverage trend and estimate the absolute inequality. Analysis was conducted using Excel and the WHO’s Health Equity Assessment Toolkit software.Setting The study setting is Nigeria.Participants Aggregated health service coverage data of women aged 15–49 years and children under 5 years of age.Outcome measures The outcome of interest is the level of coverage of RMNCH services in Nigeria and the difference in equity gaps among subgroups before and after UHC adoption.Results The RMNCH index increased by 6.4% points with a difference of 33.7% points to attain the minimum 80.0% target. The widest inequality was by economic status with the difference ranging from 21.9% points (95% CI 10.1% to 33.8%) to 56.3% points (95% CI 51.5% to 61.2%), Absolute Concentration Index from 3.5% points (95% CI 1.6% to 5.5%) to 11.3% points (95% CI 10.4% to 12.2%), Slope Index of Inequality from 23.1% points (95% CI 11.9% to 34.2%) to 65.5% points (95% CI 62.6% to 68.5%) and population attributable risk from 9.3% points (95% CI 7.3% to 11.4%) to 31.2% points (95% CI 29.0% to 33.3%). Among the indicators, three doses of diphtheria–tetanus–toxoid–pertussis immunisation had the widest absolute inequality across the subgroups.Conclusion The poor coverage of RMNCH services in Nigeria and persistent inequalities pinpoint the need to investigate further the country-level determinant of RMNCH service coverage. In addition, it emphasises the need to formulate effective policies focusing on marginalised groups and improving resource allocation to ensure sustainable service coverage.